Burke III, Ed., Struggle And Survival In The Modern Middle East; Smith Palestine And The Arab-Israeli Conflict - Allen, Calvin (Teaching History: A Journal of Methods, 1994)
Both of these books deal with the theme of struggle in Middle Eastern society. The volume edited by Edmund Burke, a professor of history at the University of California, Santa Cruz, presents 24 short biographies, by 27 authors, of individuals struggling to survive the wide variety of economic, social, and political conditions of the modern Middle East. Charles Smith, a history professor at San Diego State University, focuses on the struggles between and among the Jewish and Arab populations of Palestine since ancient time.